Periosteal and endosteal microcirculatory injury following excessive osteosynthesis. (March 2021) - Greksa, Ferenc; Butt, Edina; Csonka, Endre; Jávor, Péter; Tuboly, Eszter; Török, László; Szabo, Andrea; Varga, Endre; Hartmann, Petra
Highlights: The microcirculatory changes of a long bone in response to excessive osteosynthesis were characterized. The concomitant perfusion changes were recorded by a laser-Doppler flowmetric device using a novel approach. Quantitative data on the extents of local flow abnormalities in a patient were provided. The relative contributions of both the endosteal and periosteal systems to the circulatory impairment in a clinical setting were demonstrated. The simultaneous impairment of both the periosteal and endosteal systems were identified in the background of fracture non-union. Abstract: Introduction: We examined the endosteal and periosteal circulations in a patient with fracture non-union who had undergone excessive osteosynthesis applications (two long plates had been placed medially and laterally on the left tibia extending from the proximal 2/7 to the distal 6/7 parts of the bone, while a tibial component of a total knee prosthesis with a long stem had been inserted at the same time). Methods: Concomitant perfusion changes were determined in the anterolateral and anteromedial periosteal sheath of the non-united bone ends and intramedullary nearest the osteosynthesis materials during their surgical removal on re-operation. The blood flow in the periosteum and endosteum was recorded by a laser-Doppler flowmetric device using a novel approach. Control measurements were made at identical points of the right tibia. Results: Considerably lower blood flow values were measured along the tibial periosteal region of the re-operated limb than on the contralateral side (the average perfusion unit (PU) was 76 vs. 106 PU, respectively). Perfusion values were markedly lower in the endosteal region (average values of approx. 30 PU) in the control tibia and were even more diminished in the re-operated tibial endosteum (average 9 PU). Conclusions: Our study was conducted to characterize the microcirculatory changes of a long bone in response to intramedullary implantation and to provide quantitative data on the insufficiency of local perfusion in a patient with fracture non-union. Our results highlight the association between local perfusion failure and the unfavorable outcome (i.e. fracture non-union), confirming that the vital aspects of the microcirculation should not be disregarded when aiming for mechanical stability. Microcirculatory measurements constitute a new area of improvement in planning the adequate treatment for fracture non-unions with an unclear aetiology. Further refinement of the laser-Doppler technique could have potential benefits for bone surgery and postoperative trauma care in the future.